Association Between Neuraxial Labor Analgesia and Neonatal Morbidity After Operative Vaginal Delivery: A Retrospective Cross-sectional Study. Issue 4 (December 2021) - Butwick, A.J.; Wong, C.A.; Lee, H.C.; Blumenfeld, Y.J.; Guo, N.
Abstract : ( Anesthesiology . 2021;134:52–60) Operative vaginal delivery can be used to avoid intrapartum delivery and the morbidities it carries, though operative vaginal delivery is associated with neonatal and maternal risks compared with spontaneous vaginal delivery. Adequate maternal analgesia is a requirement for operative vaginal delivery, and neuraxial analgesia is the most common choice. Neuraxial analgesia may cause pelvic muscle relaxation and reduce the likelihood of neonatal injury and morbidity. This study investigated the association of neuraxial analgesia with risk of neonatal morbidity in patients undergoing vaginal delivery.